Analisis Filogenetik Cacing Parasit Anisakis spp. Pada ikan di Pesisir Selatan Yogyakarta - Septianto Wikan Nurhidayat (Science: Indonesian Journal of Science, 2025)
The third-stage larvae of Anisakis spp. are commonly found infecting marine fish, which serve as intermediate hosts. This study aimed to identify Anisakis spp. through sequencing analysis. A total of 15 specimens of hairtail (Trichiurus lepturus) and 15 specimens of red snapper (Lutjanus malabaricus) were examined to detect the presence of Anisakis spp. Fish samples were obtained from fishermen in the Glagah and Trisik, Kulonprogo, Yogyakarta. The examination involved dissection of internal organs, including the body cavity, digestive tract, liver, reproductive tract, and muscle tissue. Larvae of Anisakis were preserved in 70% ethanol. The prevalence of infection in hairtail and red snapper was 33.33% and 6.67%, respectively, with mean intensities of 4.8 and 2 larvae per fish, respectively. Genomic DNA was extracted from four Anisakis larvae using the Wizard Genomic DNA Extraction and Purification Kit (Promega). Polymerase chain reaction (PCR) and sequencing were performed targeting the mitochondrial cox2 gene. Sequence analysis of the cox2 region, combined with phylogenetic analysis, revealed that all examined specimens were identified as Anisakis typica.